Analisis integral del riesgo a deslizamientos e inundaciones en la microcuenca del rio Gila, Honduras - Salgado, R.A.=700 1 Velasquez, S.; Jimenez, F.; Faustino, J.
(Es, En)
Ilus., 11 ref.
Keywords: DESLIZAMIENTO DE TIERRAS; INUNDACION; DESASTRES; RIESGO; HONDURAS; VULNERABILIDAD; MICROCUENCAS